2020
DOI: 10.1093/ecco-jcc/jjz203.019
|View full text |Cite
|
Sign up to set email alerts
|

OP20 The gut microbiota during biological therapy for inflammatory bowel disease

Abstract: Background The expansion of therapeutic options in IBD brought forward a need to personalise treatment. Gut inflammation in inflammatory bowel disease (IBD) patients has been associated with reduced microbial richness and abundance of SCFA producers. We aimed to explore the longitudinal impact of treatment on the inflammatory burden and faecal microbiota in patients with CD and UC, treated with anti-tumour necrosis factor (anti-TNF) therapy, vedolizumab (VDZ) or ustekinumab (UST). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Similarly, in ulcerative colitis, the principal components of the microbiome normalize after achieving long-term, but not short-term remission (36). In a very recent study, it appeared that microbial normalization upon achieving remission was much more pronounced following anti-TNF treatment compared to vedolizumab and ustekinumab treatment (16). Some studies, including the latter, found an association between the pre-therapy microbiome and therapy response but a solid prediction using the bacterial composition data alone is still not available (16).…”
Section: Dysbiosis In Ibd With and Without Inflammationmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, in ulcerative colitis, the principal components of the microbiome normalize after achieving long-term, but not short-term remission (36). In a very recent study, it appeared that microbial normalization upon achieving remission was much more pronounced following anti-TNF treatment compared to vedolizumab and ustekinumab treatment (16). Some studies, including the latter, found an association between the pre-therapy microbiome and therapy response but a solid prediction using the bacterial composition data alone is still not available (16).…”
Section: Dysbiosis In Ibd With and Without Inflammationmentioning
confidence: 99%
“…In a very recent study, it appeared that microbial normalization upon achieving remission was much more pronounced following anti-TNF treatment compared to vedolizumab and ustekinumab treatment (16). Some studies, including the latter, found an association between the pre-therapy microbiome and therapy response but a solid prediction using the bacterial composition data alone is still not available (16). When taken together, a large part of the alterations observed in the IBD microbiome appear to be reversible and secondary to inflammation.…”
Section: Dysbiosis In Ibd With and Without Inflammationmentioning
confidence: 99%
See 1 more Smart Citation